Divergent LIN28-mRNA associations result in translational suppression upon the initiation of differentiation - Tan, S.; Altschuler, G.; Zhao, T.; Ang, H.; Yang, H.; Lim, B.; Vardy, L.; Hide, W.; Thomson, A.; Lareu, Ricky R. (Oxford University Press, 2014)
LIN28 function is fundamental to the activity and behavior of human embryonic stem cells (hESCs) and induced pluripotent stem cells. Its main roles in these cell types are the regulation of translational efficiency and let-7 miRNA maturation. However, LIN28-associated mRNA cargo shifting and resultant regulation of translational efficiency upon the initiation of differentiation remain unknown. An RNA-immunoprecipitation and microarray analysis protocol, eRIP, that has high specificity and sensitivity was developed to test endogenous LIN28-associated mRNA cargo shifting. A combined eRIP and polysome analysis of early stage differentiation of hESCs with two distinct differentiation cues revealed close similarities between the dynamics of LIN28 association and translational modulation of genes involved in the Wnt signaling, cell cycle, RNA metabolism and proteasomal pathways. Our data demonstrate that change in translational efficiency is a major contributor to early stages of differentiation of hESCs, in which LIN28 plays a central role. This implies that eRIP analysis of LIN28-associated RNA cargoes may be used for rapid functional quality control of pluripotent stem cells under manufacture for therapeutic applications.